Movement Coordination: Factor Structure of Development in 5th-7th Grade Girls - O. Ivashchenko; V. Prykhodko; M. Cieslicka (OVS LLC, 2018)
The study objective is to determine the structure of coordination abilities development in 5th-7th grade girls. Materials and methods. The participants in the study were 5th grade girls (n = 20), 6th grade girls (n = 23), 7th grade girls (n = 19). The study used the following methods: analysis and collation of scientific and methodological literature, general scientific methods of theoretical level, such as analogy, analysis, synthesis, abstraction, induction, as well as general scientific methods of empirical level: observation, testing, experiment. To evaluate motor preparedness, the study recorded the results of motor tests, body height and weight. The IBM SPSS 20 statistical analysis software was used to process the study materials. A factor analysis was performed, for which the study used principal component analysis with the rotation method: Variamax with Kaiser Normalization. Results. The analysis of similarities shows that the most informative tests in the structure of motor preparedness of the 5th grade girls are the following: test 11 "Evaluation of the ability for vestibular (statokinetic) stability. Running with turns" (.884), test 9 "Static equilibrium evaluation by E. Ya. Bondarevsky's method" (.826), test 6 "Evaluation of the sense of movement speed in sprinting" (.824); of the 6th grade girls - test 11 "Evaluation of the ability for vestibular (statokinetic) stability. Running with turns" (0.884), test 9 "Static equilibrium evaluation by E. Ya. Bondarevsky's method" (.826), test 6 "Evaluation of the sense of movement speed in sprinting" (.824); of the 7th grade girls - test 8 "Evaluation of the ability to differentiate movement speed (reproduction accuracy of running speed at 90% intensity of maximum)" (.902), test 11 "Evaluation of the ability for vestibular (statokinetic) stability. Running with turns" (.900), test 1 "30 m running (s)" (.869). Conclusions. In the structure of coordination abilities of the 5th-7th grade girls, the most informative components are the sense and differentiation of running speed, vestibular stability in exercises that require static and dynamic equilibrium. To carry out pedagogical control of coordination preparedness of 5th-7th grade girls, the study recommends using the following tests: test 11 "Evaluation of the ability for vestibular (statokinetic) stability. Running with turns", test 9 "Static equilibrium evaluation by E. Ya. Bondarevsky's method", test 6 "Evaluation of the sense of movement speed in sprinting".